Preventing cardiovascular events after pneumonia with aspirin: one step forward, but still many to go. Issue 2 (11th February 2021) - Kolditz, Martin; Welte, Tobias
Cardiovascular (CV) diseases and lower respiratory tract infections dominate human burden of disease across the world. Combined, they cause nearly 20 million or 36% of annual global deaths [1]. Additionally, both are linked together and interact bidirectionally: underlying CV disease is an established risk factor for the development of pneumonia and poor prognosis during pneumonia [2, 3], and vice versa, the role of pneumonia as risk factor for CV complications and new-onset CV disease has been demonstrated [4–6]. Preventing cardiovascular events after pneumonia by aspirin: another step forward, but questions remain https://bit.ly/2H5z4OB